Casos de violencia psicológica contra la mujer en la sede fiscal de Iquitos 2023 - Ramirez Cerron, Klaus Jonas (2025)
This study examines the handling of psychological violence cases against women at the Public Prosecutor's office in Iquitos, identifying key barriers and proposing improvements to optimize judicial attention. Using a quantitative, non-experimental, and longitudinal approach, 80 case files were analyzed, and surveys were conducted with judicial operators. It was found that 70% of the dismissals were due to a lack of conclusive evidence, highlighting the critical issue of insufficient evidence collection. Additionally, 38.8% of victims experienced revictimization during the judicial process, linked to failures in psychological and legal support. Although 70% of the cases had protective measures in place, 40% of these were ineffective due to the aggressor's non compliance or lack of supervision. The correlation between dismissals and judicial system inefficiency emphasizes the urgent need to improve judicial processes. This study validates the initial hypotheses and underscores the importance of training judicial operators, implementing effective supervision mechanisms, and ensuring compliance with protective measures. The findings provide a framework to develop strategies that strengthen the judicial system and ensure the safety and well-being of victims in Iquitos.